A Reexamination of In Vitro Fertilization - Muñoz, Michael G. (Christian bioethics, 2023)
For the sake of consistency with settled principles from other theological and ethical questions, there is a need for a Christian reexamination of in vitro fertilization (IVF). Both Old and New Testaments demonstrate that human personal life begins at conception or fertilization. Additionally, the Bible teaches that human beings are persons in the image of God from the very beginning of their existence. Thus, it can be concluded that the embryos created via IVF are persons in God’s image. Applying this to the destruction and freezing of embryos, several limitations or restrictions present themselves—embryos should not be purposefully destroyed or wasted, all embryos ought to be implanted, and embryos should not be frozen. Ultimately, however, due to the immense quantity of embryo wastage, it is concluded that Christians should avoid this form of assisted reproductive technology and consider it a pro-life issue.